Higher plant Ca(2+)-ATPase: primary structure and regulation of mRNA abundance by salt. - Wimmers, L E (1992)
Calcium-dependent regulatory mechanisms participate in diverse developmentally, hormonally, and environmentally regulated processes, with the precise control of cytosolic Ca2+ concentration being critical to such mechanisms. In plant cells, P-type Ca(2+)-ATPases localized in the plasma membrane and the endoplasmic reticulum are thought to play a central role in regulating cytoplasmic Ca2+ concentrations. Ca(2+)-ATPase activity has been identified in isolated plant cell membranes, but the protein has not been characterized at the molecular level. We have isolated a partial-length cDNA (LCA1) and a complete genomic clone (gLCA13) encoding a putative endoplasmic reticulum-localized Ca(2+)-ATPase in tomato. The deduced amino acid sequence specifies a protein (Lycopersicon Ca(2+)-ATPase) of 1048 amino acids with a molecular mass of 116 kDa, eight probable transmembrane domains, and all of the highly conserved functional domains common to P-type cation-translocating ATPases. In addition, the protein shares approximately 50% amino acid sequence identify with animal sarcoplasmic/endoplasmic reticulum Ca(2+)-ATPases but less than 30% identity with other P-type ATPases. Genomic DNA blot hybridization analysis indicates that the Lycopersicon Ca(2+)-ATPase is encoded by a single gene. RNA blot hybridization analysis indicates the presence of three transcript sizes in root tissue and a single, much less abundant, transcript in leaves. Lycopersicon Ca(2+)-ATPase mRNA levels increase dramatically upon a 1-day exposure to 50 mM NaCl. Thus this report describes the primary structure of a higher-plant Ca(2+)-ATPase and the regulation of its mRNA abundance by salt stress.